2022
DOI: 10.3390/molecules27185788
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity Tuning by Natural Deep Eutectic Solvents (NADESs) for Extraction of Bioactive Compounds from Cytinus hypocistis—Studies of Antioxidative, Enzyme-Inhibitive Properties and LC-MS Profiles

Abstract: In the present study, the extracts of Cytinus hypocistis (L.) L using both traditional solvents (hexane, ethyl acetate, dichloromethane, ethanol, ethanol/water, and water) and natural deep eutectic solvents (NADESs) were investigated in terms of their total polyphenolic contents and antioxidant and enzyme-inhibitive properties. The extracts were found to possess total phenolic and total flavonoid contents in the ranges of 26.47–186.13 mg GAE/g and 0.68–12.55 mg RE/g, respectively. Higher total phenolic content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 51 publications
0
8
1
Order By: Relevance
“…When comparing conventional and DESs for TPC, the highest content from DES extracts (in DES 6) was 67 %, 75 %, and 182 % higher, respectively, compared to the values obtained from ethanol, methanol, and water extract. Similarly, in a study published by Zengin et al., [43] the total phenolic contents and antioxidant activities of Cytinus hypocistis (L.) extracts were determined using natural deep eutectic solvent (NADESs). The researchers compared the results obtained with NADESs with the results of different conventional solvents such as hexane, ethyl acetate, dichloromethane, ethanol, ethanol/water, and water.…”
Section: Resultsmentioning
confidence: 99%
“…When comparing conventional and DESs for TPC, the highest content from DES extracts (in DES 6) was 67 %, 75 %, and 182 % higher, respectively, compared to the values obtained from ethanol, methanol, and water extract. Similarly, in a study published by Zengin et al., [43] the total phenolic contents and antioxidant activities of Cytinus hypocistis (L.) extracts were determined using natural deep eutectic solvent (NADESs). The researchers compared the results obtained with NADESs with the results of different conventional solvents such as hexane, ethyl acetate, dichloromethane, ethanol, ethanol/water, and water.…”
Section: Resultsmentioning
confidence: 99%
“…Their results showed that the applied DES was much more effective in tannic acid extraction than methanol when the same parameters were applied (641.16 µ/g vs. 368.99 µg/g) [ 206 ]. Further optimization led to even higher tannic acid yield [ 207 ]. Most of the previously mentioned research has investigated different types of DESs in the extraction of desired compounds, while here, the authors used one type of DES, changing only the component ratio.…”
Section: Extraction Of Tannins Using Deep Eutectic Solventsmentioning
confidence: 99%
“…Yellow cytinus ( Cytinus hypocistis L.) is a plant used in traditional medicine, due to its potential health benefits. In traditional medicine, it is used for dysentery treatment, to reduce inflammation, and for healing scars, and it is known for its high content of tannins [ 207 ]. Zengin et al compared different solvents, both conventional (hexane, ethyl acetate, dichloromethane, ethanol, ethanol/water, and water) and NADESs (choline chloride:urea, L-proline:xylitol protonated with HCl, and L-proline:xylitol protonated with H 2 SO 4 ) for extraction of bioactive compounds from Cytinus hypocistis (L.).…”
Section: Extraction Of Tannins Using Deep Eutectic Solventsmentioning
confidence: 99%
“…Poorly water-soluble compounds can be extracted from plant biomass in high concentrations and afterwards separated from the (Na)DES by addition of water and subsequent compound precipitation. Thus, (Na)DES, alone or in combination with other methods, can be used to extract various compounds like polyphenols, 47–51 pigments, 52 enzymes 53 and carbohydtrates. 50 Their high solubilizing capacity can be exploited to overcome limited substrate solubility in enzymatic reactions 54 as well as for separation techniques.…”
Section: Localization and Compound Solubility – Why Nades Are Believe...mentioning
confidence: 99%